2018
DOI: 10.1159/000491536
|View full text |Cite
|
Sign up to set email alerts
|

Leupaxin Promotes Bladder Cancer Proliferation, Metastasis, and Angiogenesis Through the PI3K/AKT Pathway

Abstract: Background/Aims: Leupaxin (LPXN) is a member of the paxillin protein family. Several studies have reported that LPXN regulates cancer development; however, the role of LPXN in bladder cancer remains unknown. Methods: The expression of LPXN in bladder cancer cells and tissues was determined by real-time PCR, western blotting, and immunohistochemistry, respectively. The biological role of LPXN in bladder cancer cell proliferation, invasion, and angiogenesis was explored both in vitro and in vivo. Results: LPXN e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…PI3K/Akt signaling pathway can act as an inducer of metastasis in several malignancies including BC cells [ 100 , 101 , 102 ]. Anti-tumor agents such as leupaxin can suppress invasion of BC cells via PI3K/Akt downregulation [ 103 ]. miRNA-328-3p is considered as an onco-suppressor factor in BC cells.…”
Section: Micrornas Inhibit Emt In Bladder Cancer Cellsmentioning
confidence: 99%
“…PI3K/Akt signaling pathway can act as an inducer of metastasis in several malignancies including BC cells [ 100 , 101 , 102 ]. Anti-tumor agents such as leupaxin can suppress invasion of BC cells via PI3K/Akt downregulation [ 103 ]. miRNA-328-3p is considered as an onco-suppressor factor in BC cells.…”
Section: Micrornas Inhibit Emt In Bladder Cancer Cellsmentioning
confidence: 99%
“…Numerous studies have confirmed that the phosphatidylinositol-3 kinase (PI3K)/Akt (protein kinase B)/mammalian target of rapamycin (mTOR) pathway plays an important role in cell proliferation, metastasis and angiogenesis in bladder cancer [8,9]. Moreover, studies have demonstrated that blocking the PI3K/Akt/mTOR pathway can be a potential therapeutic strategy [10].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/AKT signaling pathway is involved in numerous diverse cellular functions, including cell proliferation (6), differentiation (7), angiogenesis (8) and autophagy (9). The PI3K/AKT signaling pathway also affects epithelial-mesenchymal transition (EMT) via multiple regulatory mechanisms, which influences tumor aggressiveness (10).…”
Section: Introductionmentioning
confidence: 99%